2010
DOI: 10.1103/physrevb.82.161416
|View full text |Cite
|
Sign up to set email alerts
|

Electron-avalanche amplifier based on the electronic Venturi effect

Abstract: Scattering of otherwise ballistic electrons far from equilibrium is investigated in a cold two-dimensional electron system. The interaction between excited electrons and the degenerate Fermi liquid induces a positive charge in a nanoscale region which would be negatively charged for diffusive transport at local thermal equilibrium. In a three-terminal device we observe avalanche amplification of electrical current, resulting in a situation comparable to the Venturi effect in hydrodynamics. Numerical calculatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…The scattering of quantum-confined electrons by phonons, both with 22,[29][30][31] and without 32,33 magnetic field, has been studied extensively. These previous studies, however, have focused on macroscopic properties such as conductance or optical absorption.…”
Section: Phonon Relaxation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering of quantum-confined electrons by phonons, both with 22,[29][30][31] and without 32,33 magnetic field, has been studied extensively. These previous studies, however, have focused on macroscopic properties such as conductance or optical absorption.…”
Section: Phonon Relaxation Ratesmentioning
confidence: 99%
“…7 it was reported that, at certain magnetic field strengths, a significant fraction of the electrons arrive at the detector with an energy that is some integermultiple of ∼36meV less than their energy at emission. Since 36meV corresponds approximately to the energy of LO phonons in GaAs 22 , it was concluded that these electrons had emitted one or more LO phonons en route to detector. Moreover, Fletcher et al 7 report that whilst these "phonon replica" features are pronounced at lower fields (B = 6T), they are scarcely visible at high fields (B = 12T).…”
Section: Introductionmentioning
confidence: 99%
“…From these results, we can figure out that during solution decomposition, the narrow waist in the cell's middle leads to increasing the flow of free electrons from the high-to low-temperature regions. Consequently, this produces an avalanche amplification of electrical current in the middle, resulting in a situation comparable to the Venturi effect in hydrodynamics [19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…While the electrons pass the barrier, the positively charged holes are trapped between BE and BC. Without a connection to the environment, a positive charge would accumulate here, 5 but since the side contact is grounded and therefore provides a reservoir of charge carriers, electrons are drawn from this contact into the device. The jet pump analogy is therefore especially appealing as it incorporates the attractive force exerted on the "fluid" in the side port.…”
Section: -mentioning
confidence: 99%
“…The electronic analogy of the Venturi effect has been introduced in Ref. 5; other experiments describing related physics but, in part, based upon different effects have been performed since the 1990s. 6,7 II.…”
Section: Introductionmentioning
confidence: 99%